(untitled) (Cardiovascular Journal, 2016)
Background: Excess of salt consumption increases blood pressure which is a leading risk for developing cardiovascular diseases. The real salt intake practice among Bangladeshi population is still unknown which demands further research. The objective of the study was to assess the salt intake pattern among the faculties and doctors of Bangladesh University of Health Sciences (BUHS). Methods: A cross-sectional study was conducted among a total of 92 faculties and doctors of BUHS in 2015 using a semi-structured, self-administered and modified version of WHO STEPS questionnaire of salt intake. The questionnaire included information regarding knowledge and practice of salt intake. Results: Among the total respondents 58% were women and 60% were academicians with mean age 41.1 ±10.6 years. The prevalence of added salt intake in meal was 28.2%. Regarding practice, 31.6% used salty sauce in meal, 52.8% used salty sauce in cooking, and 41.8% consumed processed food with high salt. But almost three fourth (72.8%) of the respondents believed that lowering salt in meal is very important and 93.5% of them believed that excess salt or salty sauce can cause a health problem. Conclusion: The respondents had overall good knowledge regarding added salt intake but the practice was low. To reduce the prevalence of added salt intake further awareness needs to be developed. Cardiovasc. j. 2016; 8(2): 94-98